How many paediatric referrals to an allergist could be managed by a general practitioner with special interest?. Issue 2 (21st December 2015) - Isinkaye, Tomide; Gilbert, Sarah; Seddon, Paul; Fox, Adam T.; Leech, Susan; Pollock, Ian; Smith, Helen
Abstract: Background: The concept of a general practitioner with special interest (GPwSI) was first proposed in the 2000 National Health Service Plan, as a way of providing specialized treatment closer to the patient's home and reducing hospital waiting times. Given the patchy and inadequate provision of paediatric allergy services in the UK, the introduction of GPwSIs might reduce pressure on existing specialist services. Methods: A total of 100 consecutive referrals to a specialist paediatric allergy clinic were reviewed to assess what proportion could be managed by a GPwSI allergy service with a predefined range of facilities and expertise (accurate diagnosis and management of allergy; skin prick testing; provision of allergen avoidance advice; ability to assess suitability for desensitization). Each referral was reviewed independently by three allergy specialists. Cases were initially judged on the referral letter and then, to determine whether appropriate triage decisions could be made prospectively, cases were re‐assessed with information summarized in the clinic letter. The proportion of referrals suitable for a GPwSI was calculated and their characteristics identified. Results: At least 42% and up to 75% were suitable for management by a GPwSI in allergy based on unanimous and majority agreement, respectively. The appropriateness of 79% referrals could be identified based on the information in the referral letter. A total of 19% referrals were unsuitable for a GPwSI service because of complex or multisystem disease, need for specialist knowledge or facilities or patient's young age. Conclusions: At least two‐fifths of paediatric allergy referrals to our hospital‐based service could be dealt with in a GPwSI clinic, thereby diversifying the patient pathway, allowing specialist services to focus on complex cases and reducing waiting times for appointments.